Health surveillance: public water supply fluoridation in 40 municipalities of Sao Paulo, Brazil - Saliba Moimaz, Suzely Adas [UNESP]; Pupim dos Santos, Luis Felipe [UNESP]; Saliba, Tânia Adas [UNESP]; Saliba, Nemre Adas [UNESP]; Saliba, Orlando [UNESP] (Abrasco-assoc Brasileira Pos-graduacao & Saude Coletiva, 2020)
Since fluoridation of water is an established public health measure for the prevention of dental caries and considering that monitoring of the method is crucial to its success, this study aimed to analyze the results of the analysis of the fluorine content of public water supply of 40 municipalities in the state of Sao Paulo, from November 2004 to December 2016. Samples were analyzed monthly using the potentiometric method. Of the 32,488 samples, 50.94% contained fluoride levels within the recommended range. In 2004, it was verified that 21 cities (52.50%) had mean levels within the recommended parameter, increasing to 32 cities (80.00%) in 2016. It was observed that 15 municipalities that initially had levels of fluoride below 0.55 mgF/L in their water supply adjusted to adequate levels during the project. In the first year of the study, 47.76% of the samples had values in the recommended range, which increased to 58.22% in 2016. Most of the municipalities adjusted the levels of fluoride in their waters over the years, evidencing the performance of heterocontrol programs as important strategies that assist in the monitoring of the method and have significant participation in the control of the water quality supplied to the population.
Keywords: Fluoridation; Public health; Oral health; Water supply